2009
DOI: 10.1378/chest.08-1881
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sarcoidosis-Associated Pulmonary Hypertension

Abstract: Background: Pulmonary hypertension (PH) is a common complication of sarcoidosis that is associated with increased mortality. The pathogenesis of PH in sarcoidosis is uncertain, and the role of pulmonary arterial hypertension (PAH)-specific therapies remains to be determined. Methods: We conducted a retrospective study of patients with sarcoidosis and PH at two referral centers. New York Heart Association (NYHA) functional class, exercise capacity, hemodynamic data, pulmonary function tests, and survival were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
96
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 27 publications
(28 reference statements)
3
96
1
9
Order By: Relevance
“…After a median of 4 months of therapy, repeat haemodynamics and 6MWD were measured. There was a significant improvement in mean pulmonary artery pressure and pulmonary vascular resistance, similar to the data reported in prior studies [15][16][17][18]. Interestingly, there was no significant change in 6MWD.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…After a median of 4 months of therapy, repeat haemodynamics and 6MWD were measured. There was a significant improvement in mean pulmonary artery pressure and pulmonary vascular resistance, similar to the data reported in prior studies [15][16][17][18]. Interestingly, there was no significant change in 6MWD.…”
supporting
confidence: 88%
“…An improvement in haemodynamics with little change in 6MWD has been noted in two prospective clinical trials that evaluated S-APH patients after 4 months of therapy [15,16]. Another study did report that some patients had improvement in their 6MWD after a median of 14 months treatment [17]. That study found that only those patients with none to moderate impairment in vital capacity had an improvement in their 6MWD.…”
mentioning
confidence: 88%
“…[1] For the remaining patients, corticosteroids alone are the first choice (10-20 mg a day), but if corticosteroidsparing agents are necessary, then methotrexate or azothioprine are the best choices. [7] In our case, the patient was diabetic. Since higher steroid doses can impair glucose levels, we preferred to begin the treatment with lower doses of corticosteroids the day after protocol.…”
mentioning
confidence: 57%
“…There is precedence for similar reports. [10][11][12] To date, prostacyclin-analog therapy has not been recommended for SCDPH due to apparent fear of high-cardiac output pulmonary edema, line sepsis, and line thrombosis. The only relevant publication is a brief report describing tolerance of continuous intravenous epoprostenol in one patient for 1.5 years.…”
Section: Letters To the Editormentioning
confidence: 99%